Preparation method of loxoprofen sodium tablet

By using a combination of low-substituted hydroxypropyl cellulose and magnesium stearate in the preparation of loxoprofen sodium tablets, combined with wet high shear granulation process, poor dissolution and dissolution of loxoprofen sodium tablets were solved. The problem of low results enables the effect of simplifying the process and reducing costs.

CN119185218APending Publication Date: 2024-12-27BEIJING YUNPENG PENGCHENG PHARM TECH CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411335419.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-24
Publication Date
2024-12-27

AI Technical Summary

Technical Problem

During the preparation process, the loxoprofen sodium tablets have problems such as poor disintegration, strong hygroscopicity and low dissolution. In the prior art, the addition of silica as a glidant affects the dissolution behavior of the main drug and increases the preparation process. Complexity and cost.

Method used

Loxoprofen sodium tablets were prepared by mixing two disintegrants (low-substituted hydroxypropyl cellulose) and combining lactose and magnesium stearate through wet high shear granulation process to improve the compressibility of the particles and Disintegrability, simplify process flow.

Benefits of technology

The good disintegration and dissolution of loxoprofen sodium tablets are achieved, the preparation cost is reduced, the process flow is simplified, and the quality reproducibility and dissolution behavior of the drug are similar to that of the reference preparation.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119185218A_ABST
    Figure CN119185218A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of medicine preparation, in particular to a preparation method of loxoprofen sodium tablets. The loxoprofen sodium tablet is prepared by the following steps: weighing lactose, ferric oxide, raw material medicines and low-substituted hydroxypropyl cellulose (LH21 and LH22 two types of disintegrating agents) according to a prescription amount, putting the materials into a wet granulator, uniformly mixing, granulating by adopting high-speed shearing, drying by controlling the temperature of the materials to be 25-40 DEG C through a fluidized bed granulating and coating machine, finishing the granules, and tabletting to obtain the loxoprofen sodium tablet. The two disintegrants are added, so that sample disintegration is met, the moldability of sample particles is improved, and process reproduction is facilitated. The traditional Chinese medicine composition is simple, only contains main medicines and conventional auxiliary materials, is safe to use, and does not increase the burden of a patient. The preparation process is simple and convenient to operate, and is a conventional high-shear wet granulation process.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of medicine preparation, and more specifically to a method for preparing loxoprofen sodium tablets. Background Art

[0002] In 1986, Daiichi Sankyo Co. Ltd. launched loxoprofen sodium tablets in Japan. It is a non-steroidal antipyretic analgesic. Compared with similar drugs in clinical practice, its main characteristics are: stronger (good clinical effect), faster (plasma concentration can reach peak value 30 minutes after oral administration), safer (few side effects); another characteristic is its wide range of indications: ① Anti-inflammatory and analgesic for the following diseases and symptoms: rheumatoid arthritis, osteoarthritis, low back pain, periarthritis of shoulder, cervical shoulder-wrist syndrome, toothache. ② Analgesia and anti-inflammatory after surgery, trauma and tooth extraction. ③ Acute upper respiratory tract inflammation (including acute upper respiratory tract inflammation accompanied by acute bronchitis).

[0003] Loxoprofen sodium chemical name: (±)-2-[p-(2-oxocyclopentylmethyl)phenyl]propionate sodium dihydrate, molecular formula and molecular weight are C 15 H 17 NaO3·2H2O / 304.31, CAS No. 226721-96-6, structural formula is as follows:

[0004]

[0005] The original Japanese patent JP2669517 mentioned that the raw material of loxoprofen sodium has strong adhesion to drug excipients, equipment, and containers during the preparation process. The patent also mentioned that adding a large amount of lubricants (such as magnesium stearate) to the prescription will affect the disintegration, solubility and bioavailability of the preparation, and when the tablets are made, the hardness is significantly reduced. Therefore, choosing a suitable prescription process is critical to the preparation of self-made products.

[0006] Since loxoprofen sodium has high viscosity, it is easy to clump after disintegration; secondly, it is easy to absorb moisture. After absorbing moisture, the tablets are fluffy and the solubility decreases significantly. In order to solve the above problems, Chinese Patent 201210123938.3 provides a loxoprofen sodium dispersion composition, which contains loxoprofen sodium and silicon dioxide, and is characterized in that the silicon dioxide is added by internal addition. Generally, silicon dioxide is used as a glidant and added by external addition, that is, it is added after granulation to increase the fluidity of the particles and reduce the resistance of tableting. The technical solution adopted by the invention is internal addition, and the amount of silicon dioxide accounts for 3%-5% (weight percentage) of the total prescription. The composition has good dispersion uniformity and stable properties. However, the addition of silicon dioxide during granulation affects the dissolution behavior of the main drug, which is different from the dissolution curve of the original drug.

[0007] 202010581439.3 discloses a loxoprofen sodium tablet, which is composed of 100-120 parts of loxoprofen sodium, 200-250 parts of microcrystalline cellulose, 8-20 parts of sophorolipids, 10-20 parts of konjac glucomannan, 15-20 parts of cross-linked polyvinylpyrrolidone and 1-5 parts of magnesium stearate; the weight ratio of sophorolipids to konjac glucomannan is 6:7.5, and the mixture of excipients and active ingredients is extruded to prepare particles by hot melt extrusion technology, and after drying, magnesium stearate in a prescribed amount is added, and loxoprofen sodium tablets are obtained by tableting and coating. The hot melt extrusion process of this process prolongs the preparation process and increases the preparation cost. Summary of the invention

[0008] In view of the above technical problems, the present invention provides a method for preparing loxoprofen sodium tablets. In the preparation method, two disintegrants are mixed and added to improve the compressibility of particles while satisfying the disintegration of the self-made product.

[0009] In order to solve the above technical problems, the technical solution adopted by the present invention is:

[0010] A preparation method of loxoprofen sodium tablets comprises the following steps: mixing a raw material drug, lactose, low-substituted hydroxypropyl cellulose and ferric oxide, granulating, drying and granulating the mixture, and then mixing the granulated mixture with magnesium stearate for tableting to obtain plain tablets; the low-substituted hydroxypropyl cellulose adopts two types of disintegrants.

[0011] Preferably, the low-substituted hydroxypropyl cellulose adopts two types of disintegrants, namely LH21 and LH22.

[0012] Preferably, the following steps are adopted to prepare:

[0013] S1. The raw materials are crushed and sieved by a hammer mill, and the ferric oxide is sieved for later use;

[0014] S2. Weigh the prescribed amount of lactose, ferric oxide, API and low-substituted hydroxypropyl cellulose and mix them evenly in a wet granulator. Use high-speed shear granulation and use purified water as the wetting agent.

[0015] S3. The wet granules obtained in step S2 are sieved and placed in a fluidized bed granulator, the air inlet temperature is set for drying, the moisture content of the granules is controlled to 4% to 6%, and the dry granules are sieved and sieved;

[0016] S4. The dry granules obtained in step S3 are placed in a hopper mixer and the prescribed amount of magnesium stearate is added and mixed evenly;

[0017] S5. The total mixed granules obtained in step S4 are tableted using a rotary tablet press to obtain plain tablets.

[0018] Preferably, the loxoprofen sodium tablets contained in S1 have a specification of 60 mg.

[0019] Preferably, the two disintegrants are added in a ratio of 9:19.

[0020] Preferably, the drug substance is loxoprofen sodium hydrate; the lactose is used as a filler; the purified water is used as a wetting agent; the low-substituted hydroxypropyl cellulose is used as a disintegrant; and the magnesium stearate is used as a lubricant.

[0021] Preferably, in S2, by weight, loxoprofen sodium accounts for 27.24%; lactose accounts for 49.85%; ferric oxide accounts for 0.004%; low-substituted hydroxypropyl cellulose accounts for 22.4%; and magnesium stearate accounts for 0.5%.

[0022] Preferably, the drying air inlet temperature in S3 is 40°C, and the material temperature is controlled at 25°C to 40°C.

[0023] Preferably, the particle size distribution of the total mixed particles in S5 is mainly distributed above 40 mesh to 80 mesh.

[0024] Preferably, the tabletting standard in S5 is 0.25 g per tablet, and the tablets are pressed using a Φ9 mm flat and oblique punch die, the main pressure of the tablet press is 20 to 60 KN, and the hardness is controlled at 40 N to 90 N.

[0025] The beneficial effects of the present invention are as follows:

[0026] The loxoprofen sodium tablet prepared by the invention contains only a main drug and conventional auxiliary materials, is safe to use, and does not increase the burden on patients. The preparation process is simple and easy to operate. Loxoprofen sodium, lactose, low-substituted hydroxypropyl cellulose and ferric oxide are mixed and then a wet high-shear granulation process is adopted. The weight and properties of the prepared drug tablets are compared with the dissolution curve of the reference preparation in the water medium, and the speed is similar.

[0027] The invention has low cost and simple process. The method of mixing and adding two disintegrants can not only meet the disintegration of the self-made product, but also improve the compressibility of the particles, which is beneficial to the quality control of the medicine and has good reproducibility. The dissolution behavior of the medicine is similar to that of the reference preparation. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] The above and / or additional aspects and advantages of the present invention will become apparent and easily understood from the description of the embodiments in conjunction with the following drawings, in which:

[0029] Figure 1 It is a comparative schematic diagram of the dissolution curves of Example 1, Example 2, Example 3 and the reference preparation (specification 60 mg) of the present invention; DETAILED DESCRIPTION

[0030] In order to more clearly understand the above-mentioned purpose, features and advantages of the present invention, the present invention is further described in detail below in conjunction with the accompanying drawings and specific embodiments. It should be noted that the embodiments of the present application and the features in the embodiments can be combined with each other without conflict.

[0031] In the following description, many specific details are set forth to facilitate a full understanding of the present invention. However, the present invention may also be implemented in other ways different from the description. Therefore, the protection scope of the present invention is not limited to the specific embodiments disclosed below.

[0032] Example 1

[0033] 1. Prescribing Information

[0034]

[0035] 2. Preparation process

[0036] (1) Processing of raw materials and auxiliary materials: The API was crushed by UPM140 hammer mill and passed through a 60-mesh sieve; the ferric oxide was passed through a 60-mesh sieve for later use.

[0037] (2) Premixing: Weigh the prescribed amount of lactose, ferric oxide, API and low-substituted hydroxypropyl cellulose and place them in a G6 wet granulator with the stirring speed set at 200 rpm and the cutting speed at 1500 rpm for mixing for 5 min.

[0038] (3) Granulation: Purified water was sprayed into a wet mixing granulator to make a soft material. The stirring speed was set to 200 rpm and the cutting speed to 1500 rpm for granulation for 1 min. The material was granulated through a ZL50 granulator with a 6*6 screen and the granulator speed was 500 rpm.

[0039] (4) Drying: The wet granules are dried using a LBL-3 fluidized bed granulator coater at an inlet air temperature of 40°C until the moisture content is 4% to 6%.

[0040] (5) Granulation: The dried granules were sieved through a 1.5 mm sieve.

[0041] (6) Total mixing: The dry granules obtained in the previous step were placed in a HSD50 hopper mixer, and the prescribed amount of magnesium stearate was added and mixed for 3 minutes.

[0042] (7) Tableting: Take the mixed material and use The round flat and oblique punches were used to press the tablets with the ZP10A rotary tablet press according to the theoretical amount, and the pressure range was controlled to be 40N to 90N.

[0043] 3. Dissolution curve determination

[0044] The in vitro dissolution experiment refers to the second method of dissolution determination in Part II 0931 of the "Chinese Pharmacopoeia 2020 Edition". The tablets prepared in Example 1 were placed in an aqueous dissolution medium for in vitro dissolution testing and compared with the original reference preparation of this product (trade name Lesong, specification 60 mg: batch number SC119LA, national medicine standard H20030769, manufacturer Daiichi Sankyo Pharmaceutical (Shanghai) Co., Ltd.). The dissolution results of Example 1 and the reference preparation are shown in Table 1, and the dissolution curves are shown in Figure 1 shown.

[0045] Example 2

[0046] 1. Prescribing Information

[0047]

[0048] 2. Preparation process

[0049] (1) Processing of raw materials and auxiliary materials: The API was crushed by UPM140 hammer mill and passed through a 60-mesh sieve; the ferric oxide was passed through a 60-mesh sieve for later use.

[0050] (2) Premixing: Weigh the prescribed amount of lactose, ferric oxide, API and low-substituted hydroxypropyl cellulose and place them in a G6 wet granulator with the stirring speed set at 200 rpm and the cutting speed at 1500 rpm for mixing for 5 min.

[0051] (3) Granulation: Purified water was sprayed into a wet mixing granulator to make a soft material. The stirring speed was set to 200 rpm and the cutting speed to 1500 rpm for granulation for 1 min. The material was granulated through a ZL50 granulator with a 6*6 screen and the granulator speed was 500 rpm.

[0052] (4) Drying: The wet granules are dried using a LBL-3 fluidized bed granulator coater at an inlet air temperature of 40°C until the moisture content is 4% to 6%.

[0053] (5) Granulation: The dried granules were sieved through a 1.5 mm sieve.

[0054] (6) Total mixing: The dry granules obtained in the previous step were placed in a HSD50 hopper mixer, and the prescribed amount of magnesium stearate was added and mixed for 3 minutes.

[0055] (7) Tableting: Take the mixed material and use The round flat and oblique punches were used to press the tablets with the ZP10A rotary tablet press according to the theoretical amount, and the pressure range was controlled to be 40N to 90N.

[0056] 3. Dissolution curve determination

[0057] The in vitro dissolution experiment refers to the second method of dissolution determination in Part II 0931 of the "Chinese Pharmacopoeia 2020 Edition". The tablets prepared in Example 1 were placed in an aqueous dissolution medium for in vitro dissolution testing and compared with the original reference preparation of this product (trade name Lesong, specification 60 mg: batch number SC119LA, national medicine standard H20030769, manufacturer Daiichi Sankyo Pharmaceutical (Shanghai) Co., Ltd.). The dissolution results of Example 1 and the reference preparation are shown in Table 1, and the dissolution curves are shown in Figure 1 shown.

[0058] Example 3

[0059] 1. Prescribing Information

[0060]

[0061] 2. Preparation process

[0062] (1) Processing of raw materials and auxiliary materials: The API was crushed by UPM140 hammer mill and passed through a 60-mesh sieve; the ferric oxide was passed through a 60-mesh sieve for later use.

[0063] (2) Premixing: Weigh the prescribed amount of lactose, ferric oxide, API and low-substituted hydroxypropyl cellulose and place them in a G6 wet granulator with the stirring speed set at 200 rpm and the cutting speed at 1500 rpm for mixing for 5 min.

[0064] (3) Granulation: Purified water was sprayed into a wet mixing granulator to make a soft material. The stirring speed was set to 200 rpm and the cutting speed to 1500 rpm for granulation for 1 min. The material was granulated through a ZL50 granulator with a 6*6 screen and the granulator speed was 500 rpm.

[0065] (4) Drying: The wet granules are dried using a LBL-3 fluidized bed granulator coater at an inlet air temperature of 40°C until the moisture content is 4% to 6%.

[0066] (5) Granulation: The dried granules were sieved through a 1.5 mm sieve.

[0067] (6) Total mixing: The dry granules obtained in the previous step were placed in a HSD50 hopper mixer, and the prescribed amount of magnesium stearate was added and mixed for 3 minutes.

[0068] (7) Tableting: Take the mixed material and use The round flat and oblique punches were used to press the tablets with the ZP10A rotary tablet press according to the theoretical amount, and the pressure range was controlled to be 40N to 90N.

[0069] 3. Dissolution curve determination

[0070] The in vitro dissolution experiment refers to the second method of dissolution determination in Part II 0931 of the "Chinese Pharmacopoeia 2020 Edition". The tablets prepared in Example 1 were placed in an aqueous dissolution medium for in vitro dissolution testing and compared with the original reference preparation of this product (trade name Lesong, specification 60 mg: batch number SC119LA, national medicine standard H20030769, manufacturer Daiichi Sankyo Pharmaceutical (Shanghai) Co., Ltd.). The dissolution results of Example 1 and the reference preparation are shown in Table 1, and the dissolution curves are shown in Figure 1 shown.

[0071] Table 1 Dissolution curve test results of examples and reference preparations

[0072]

[0073] The dissolution rate of the self-made products of Example 1 and Example 2 in 30 minutes was 100.87% and 107.01, both greater than 85%, similar to the reference preparation. The dissolution rate of the self-made product of Example 3 in 30 minutes was 69.88%, less than 85%, which was not similar to the reference preparation.

[0074] Example 3 The total mixed particles were screened using sieves of different mesh sizes for the three batches of samples. The particle distribution test is shown in Table 2 below. Table 2 Result of particle distribution test of the total mixed particles in Example

[0075]

[0076] The particle size distribution of Examples 1 and 3 is mostly between 40 and 80 meshes, while the particle size distribution of Example 2 is mostly less than 80 meshes.

[0077] Conclusion: Example 2 and Example 3 use the same type of disintegrant to prepare samples. The sample of Example 2 dissolves faster than the reference preparation, and the prepared particles have more fine powder <80 mesh; the sample of Example 3 disintegrates significantly slower than the reference preparation. Example 1 uses two disintegrants (LH22:LH21) in a ratio of 9:19 to prepare the sample. The dissolution is similar to the reference preparation, and the prepared particles have a particle size distribution of more 40 mesh to 80 mesh, less material fine powder, and better particle compressibility.

[0078] Since the drug substance of this product has high viscosity, low-substituted hydroxypropyl cellulose is mainly used as a binder and disintegrant, and the dosage in this product is 56 mg / tablet. SH-LH21 type disintegrant is mainly used as a binder and disintegrant for wet granulation. SH-LH22 type disintegrant has a lower degree of substitution and is used when a large adhesive force is not required. The viscosity of the two types of disintegrants LH22 is slightly higher than that of LH21, but the disintegration of LH21 is stronger than that of LH22. The self-made product uses two types of disintegrants to add together to prepare granules, which not only meets the disintegration of the sample, but also ensures the granule formability and compressibility.

[0079] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may also have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A method for preparing loxoprofen sodium tablets, characterized in that: The raw material drug, lactose, low-substituted hydroxypropyl cellulose and ferric oxide are mixed, granulated, dried and sized, and then mixed with magnesium stearate for tableting to obtain plain tablets; the low-substituted hydroxypropyl cellulose adopts two types of disintegrants.

2. The method for preparing a loxoprofen sodium tablet according to claim 1, wherein: The low-substituted hydroxypropyl cellulose adopts two types of disintegrants, namely LH21 and LH22.

3. A method for preparing a loxoprofen sodium tablet according to claim 1, characterized in that, Prepared using the following steps: S1. The raw materials are crushed and sieved by a hammer mill, and the ferric oxide is sieved for later use; S2. Weigh the prescribed amount of lactose, ferric oxide, API and low-substituted hydroxypropyl cellulose and place them in a wet granulator to mix evenly, and use high-speed shear granulation, with purified water as the wetting agent; S3. The wet granules obtained in step S2 are sieved and placed in a fluidized bed granulator, the air inlet temperature is set for drying, the moisture content of the granules is controlled to 4% to 6%, and the dry granules are sieved and sieved; S4. The dry granules obtained in step S3 are placed in a hopper mixer and the prescribed amount of magnesium stearate is added and mixed evenly; S5. The total mixed granules obtained in step S4 are tableted using a rotary tablet press to obtain plain tablets.

4. The method for preparing a loxoprofen sodium tablet according to claim 3, wherein: The S1 contains loxoprofen sodium tablets with a specification of 60 mg.

5. A method for preparing a loxoprofen sodium tablet according to any one of claims 1 to 4, characterized in that: The addition ratio of the two disintegrants is 9:

19.

6. A method for preparing a loxoprofen sodium tablet according to any one of claims 1 to 4, characterized in that: The raw material drug is loxoprofen sodium hydrate; the lactose is used as a filler; the purified water is used as a wetting agent; the low-substituted hydroxypropyl cellulose is used as a disintegrant; and the magnesium stearate is used as a lubricant.

7. A method for preparing a loxoprofen sodium tablet according to any one of claims 1 to 4, characterized in that: In S2, by weight, loxoprofen sodium accounts for 27.24%; lactose accounts for 49.85%; ferric oxide accounts for 0.004%; low-substituted hydroxypropyl cellulose accounts for 22.4%; and magnesium stearate accounts for 0.5%.

8. A method for preparing loxoprofen sodium tablets according to claim 3, characterized in that: In said S3, the drying air inlet temperature is 40°C, and the material temperature is controlled at 25°C to 40°C.

9. A method for preparing loxoprofen sodium tablets according to claim 3, characterized in that: The particle size distribution of the total mixed particles in S5 is mainly distributed above 40 mesh to 80 mesh.

10. The method for preparing loxoprofen sodium tablets according to claim 3, characterized in that: The standard of tableting in S5 is 0.25g per tablet, and the tablets are pressed with a Φ9mm flat and oblique punch die. The main pressure of the tablet press is 20-60KN and the hardness is controlled at 40N-90N.

Citation Information

Patent Citations

  • Loxoprofen sodium composition

    CN102670531A

  • Loxoprofen sodium tablet and preparation process thereof

    CN111700868A